Death race [videorecording (DVD)] - Anderson, Paul, 1965-; Statham, Jason, 1967-; Allen, Joan, 1956-; McShane, Ian, 1942-; Melchior, Ib; Thom, Robert, 1929-1979; Griffith, Charles B. (Universal Studios Home Entertainment, 2008)
Private corporations run most of the prisons across the U.S. for profit. Jensen Ames is framed for his wife's murder on the same day that the steel mill he works at closes. Ames is sent to prison where he is coerced by Hennessey, the sadistic prison warden, to drive a Ford Mustang and become known as the famous masked driver, Frankenstein. She tells Ames that she knows his baby was left in foster care, but that prisoners are freed upon winning five Death Races. Since he will take on the mask of the legendary Frankenstein, who had 4 wins at the time of his death, he will only need to win one race. It's a race to the finish and only the winner survives.